EFFECT OF ENVIRONMENTAL POLLUTION ON ENVIRONMENTAL QUALITY IN INDONESIA IN 2018 - Puniasih, Dhina; Prakoso, Jalu Aji (Transpublika Publisher, 2022)
The decline in environmental quality can be influenced by many things, one of which is economic growth. In 2016 Indonesia was in position 57 out of 61 countries with an environmental quality index value of 66.55. The purpose of this research is to determine the effect of Water Pollution Index (X1), Soil Pollution Index (X2), and Air Pollution Index (X3) on Environmental Quality (Y). This type of research is quantitative with an Ordinary Least Square (OLS) approach. The population in this study were 34 provinces in Indonesia with secondary data obtained from the Ministry of Environment and Forestry (KLHK) and the Central Statistics Agency (BPS) in 2018. The results of this study show that the Water Quality Index variable has an insignificant negative effect, the Soil Quality Index no significant positive effect, and the Air Quality Index variable has a significant negative effect on environmental quality. The conclusion of this study is that the government needs to implement policies in dealing with cases of water, soil, and air pollution because this is very dangerous for living things and the environment.